The scientific revolution - Shapin, Steven; Ohio Library and Information Network (Chicago, IL : University of Chicago Press, 1996)
& Quot;There was no such thing as the Scientific Revolution, and this is a book about it." With this provocative and apparently paradoxical claim, Steven Shapin begins his bold vibrant exploration of the origins of the modern scientific worldview. "Shapin's account is informed, nuanced, and articulated with clarity. ... This is not to attack or devalue science but to reveal its richness as the human endeavor that it most surely is. . . .Shapin's book is an impressive achievement."?David C. Lindberg, Science. "Shapin has used the crucial 17th century as a platform for prese
THE SCIENTIFIC REVOLUTION; Contents; List of Illustrations; Photo Credits; Acknowledgments; Introduction; ONE What Was Known?; TWO How Was It Known?; THREE What Was the Knowledge For?; Bibliographic Essay; Index
Includes bibliographical references and index
Keywords: Science -- History; Electronic books; Electronic books